An innovative approach: cow/oat milk based kefir - Nayil Dinkçi; Harun Kesenkaş; Figen Korel; Özer Kınık (Mljekarstvo)
The aim of this study was to evaluate the potential of kefir production using cow-oat milk mixture. Therefore kefir samples with 20, 40 and 60 % of oat milk were produced. The effect of oat-milk ratio on physicochemical, rheological, microbiological and sensory characteristics of the kefir samples was studied during 21 days storage at refrigerated conditions. Increasing oat milk concentration affected the whey-off and apparent viscosity by higher whey off and lower viscosity results. Also the proteolytic activity of the samples was decreased by raising the oat milk concentrations. Increase of the oat milk concentration leaded to a decrease of pH of the samples. Statistical analysis showed that the lactococci and lactobacilli viable cell counts differed among the samples while the highest count was detected in sample with the highest amount of oat milk. The control sample (without oat milk) had higher yeast count during the storage period. The final product with 20 % of oat-milk and without addition of flavour was found to be the most acceptable by the sensory panellists. The results indicate the possibility for a new cow/oat milk based kefir.